Utilization of Household Waste as Economic Added Value in Community Care for the Environment Sumber Subdistrict Cirebon Regency - Syaeful Bakhri; Dangi Dangi (LPPM Universitas Muhammadiyah Tasikmalaya, 2021)
The purpose of this activity is to convey the success of the Kopeling youth program (Community Care for the Environment) along with all the people who have supported them, especially those in the RT.05/RW.05 Kelurahan Sumber to convert household waste into compost and catfish farming feed to have a selling value. The research method uses a qualitative approach with the Participatory Research Appraisal research design through the Participatory Rural Appraisal method. This research was conducted on Kopeling youth and communities in the neighborhood RT.05/RW.05 Kelurahan Sumber. The findings obtained from this activity are that Kopeling and related communities have active participation and real motivation to minimize the problem of piles of garbage, especially household waste, to be something of economic value.